2020
DOI: 10.1039/d0ra00691b
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity evaluation and mode of action study of novel thiazole-quinolinium derivatives

Abstract: A new series of thiazole-quinolinium derivatives perturb the polymerization of FtsZ with strong antibacterial activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The result suggested that among the synthesized compounds, 47a and 47b were the most potent and effective bacteriostatic agents against multi-drug resistant bacteria. In brief, the SAR study emphasized the requirements of small groups such as CH 3 or H at the 2-position of the quinoline fragment [91]. The novel methylthiazole-based thiazolidinones derivatives were synthesized when a solution of 2-amino-5-methylthiazole and sodium carbonate in anhydrous dimethylformamide (DMF) was added dropwise to a solution of chloroacetyl chloride in DMF, and the product obtained was exploited for multistep reactions to obtain the target compounds.…”
Section: Thiazoles As Antimicrobial Agentsmentioning
confidence: 99%
“…The result suggested that among the synthesized compounds, 47a and 47b were the most potent and effective bacteriostatic agents against multi-drug resistant bacteria. In brief, the SAR study emphasized the requirements of small groups such as CH 3 or H at the 2-position of the quinoline fragment [91]. The novel methylthiazole-based thiazolidinones derivatives were synthesized when a solution of 2-amino-5-methylthiazole and sodium carbonate in anhydrous dimethylformamide (DMF) was added dropwise to a solution of chloroacetyl chloride in DMF, and the product obtained was exploited for multistep reactions to obtain the target compounds.…”
Section: Thiazoles As Antimicrobial Agentsmentioning
confidence: 99%
“…From previous studies, it was clear that thiazole and quinolinium groups are important for antibacterial activity. Li et al synthesized various thiazole-quinolinium derivatives and evaluated their antibacterial activities against Gram positive and Gram negative species ( Li et al, 2015 ). All compounds showed good antibacterial activity (MIC 1–32 μg/mL) against S. aureus.…”
Section: Quinoline Ring Compoundsmentioning
confidence: 99%
“…methylpiperidin-1-yl)propyl)benzo[d]thiazol-2(3H)-ylidene)methyl)quinolin-1-ium iodide was synthesized according to the procedures reported previously. 50 The compound was obtained as a dark brown solid with 62% yield. 1 H NMR (400 MHz, DMSO-d 6 ) δ 10.14 (s, 0.79H), 8.71 (s, 1H), 8.19 (d, J = 8.5 Hz, 1H), 8.08 (d, J = 8.5 Hz, 1H), 8.01−7.98 (t, J = 7.7 Hz, 1H), 7.83 (d, J = 8.5 Hz, 2H), 7.75 (t, J = 7.7 Hz, 2H), 7.68 (s, 1H), 7.65−7.54 (m, 4H), 7.39 (t, J = 7.7 Hz, 1H), 6.93−6.86 (m, 3H), 4.64 (m, 2H), 4.17 (s, 3H), 2.14 (m, 2H), 1.75−1.57 (m, 3H), 1.22 (m, 6H), 0.88 (m, 5H).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…quinolin-1-ium iodide was synthesized according to the procedures reported previously. 50 The compound was obtained as a dark brown solid with 63% yield. 1 UV−Visible and Fluorescence Assays.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%